Attoampere Nanoelectrochemistry: Attoampere Nanoelectrochemistry (Small 29/2021). Issue 29 (22nd July 2021) - Grall, Simon; Alić, Ivan; Pavoni, Eleonora; Awadein, Mohamed; Fujii, Teruo; Müllegger, Stefan; Farina, Marco; Clément, Nicolas; Gramse, Georg
Abstract : High frequency (GHz) signals are sent to a scanning tunneling microscope probe down to the surface of an alkylferrocene self‐assembled monolayer in liquid and allow to measure locally electrochemical charge transfer corresponding to currents on the order of attoampere. This technique, presented in article number 2101253 by Nicolas Clément, Georg Gramse, and co‐workers, opens the way to unprecedented precision for local measurements in biology, electrochemistry and materials science.